Increased Left Ventricular Mass Index Is Associated With Compromised White Matter Microstructure Among Older Adults - Elizabeth E. Moore; Dandan Liu; Kimberly R. Pechman; James G. Terry; Sangeeta Nair; Francis E. Cambronero; Susan P. Bell; Katherine A. Gifford; Adam W. Anderson; Timothy J. Hohman; John Jeffrey Carr; Angela L. Jefferson (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2018)
Background Left ventricular (LV) hypertrophy is associated with cerebrovascular disease and cognitive decline. Increased LV mass index is a subclinical imaging marker that precedes overt LV hypertrophy. This study relates LV mass index to white matter microstructure and cognition among older adults with normal cognition and mild cognitive impairment. Methods and Results Vanderbilt Memory & Aging Project participants free of clinical stroke, dementia, and heart failure (n=318, 73±7 years, 58% male, 39% mild cognitive impairment) underwent brain magnetic resonance imaging, cardiac magnetic resonance, and neuropsychological assessment. Voxelwise analyses related LV mass index (g/m2) to diffusion tensor imaging metrics. Models adjusted for age, sex, education, race/ethnicity, Framingham Stroke Risk Profile, cognitive diagnosis, and apolipoprotein E–ε4 status. Secondary analyses included a LV mass index×diagnosis interaction term with follow‐up models stratified by diagnosis. With identical covariates, linear regression models related LV mass index to neuropsychological performances. Increased LV mass index related to altered white matter microstructure (P<0.05). In models stratified by diagnosis, associations between LV mass index and diffusion tensor imaging were present among mild cognitive impairment participants only (P<0.05). LV mass index was related only to worse visuospatial memory performance (β=−0.003, P=0.036), an observation that would not withstand correction for multiple testing. Conclusions In the absence of prevalent heart failure and clinical stroke, increased LV mass index corresponds to altered white matter microstructure, particularly among older adults with clinical symptoms of prodromal dementia. Findings highlight the potential link between subclinical LV remodeling and cerebral white matter microstructure vulnerability.